Hynoparenting untuk meningkatkan pengetahuan Ibu dalam membentuk Karakter anak - Pratiwi, Kuniasari; Rahmawati, Isabella (Jurnal Kesehatan Samodra Ilmu (JKSI), 2022)
Phenomena that occur in society, most children's problems are caused by mistakes or ignorance of parents and the closest environment in how to communicate and convey good values ​​to children. shows deviations, does not follow parental advice or even fights, new parents panic and look for solutions. This should be avoided, children's character education should be carried out early before it is too late. The basic problem is that many parents do not understand when the time is right and how to educate children's character. One method that is expected to be a solution is the hypnoparenting technique. Hypnoparenting is a hypnotherapy technique that is specifically applied by parents in raising children. Broadly speaking, this technique is useful in improving the quality of communication and spiritual intelligence of parents and children. This method works directly on the child's subconscious, so that parents can apply their child's character education without coercion. This study aims to test the effectiveness of hypnoparenting counseling to increase parental knowledge in shaping children's character. This research was conducted in Al Wafa Kindergarten with the respondents being parents or guardians of Al Wafa Kindergarten students. This research is a pre-experimental study with a pretest-post test one group design. The interventions provided were in the form of counseling with interesting materials, video screenings, demonstrations, role plays, and sharing sessions. The results showed that there was a difference in knowledge before and after being given hypnoparenting counseling. The results of the paired T test showed a t-value of 7.023 (p-value 0.000 less than 0.05). Thus, it can be concluded that there is a significant difference between knowledge about mother's knowledge in shaping the child's character before and after being given counseling